Sink bathing burns: A unique opportunity for an injury prevention initiative. Issue 8 (December 2020) - Borg, Breanna A.; Durgham, Michael; Shanti, Christina M.; Klein, Justin D.
Highlights: Children are among the most vulnerable to burns. Young children are more susceptible to scald burn-related injuries while bathing. Families of low socioeconomic means are disproportionately affected by sink-bathing burns. These burns manifest in predictable patterns, consistent with their unintentional nature. Promoting prevention through safer bathing practices. Abstract: Sink-bathing is common practice among parents. However, this puts infants and young children at unrecognized risk for burn injuries. As the only verified pediatric burn center in a large urban area, we treat burn patients from a large variation in socioeconomic status. This provides us a unique opportunity to examine sink-burn injury patterns, circumstances surrounding these burns, identify areas with high incidence and put in place an injury prevention outreach initiative. This retrospective study included patients treated for sink-bathing burns at our burn center in an 8.5-year period. Analysis of 71 patients revealed infants under one year of age are most commonly afflicted. Additionally, that families of low-socioeconomic means are disproportionately affected. Understanding the different circumstances surrounding sink-bathing burns allows us to be more specific in our community education efforts and efficiently guide our resources.